2020
DOI: 10.1002/ajp.23096
|View full text |Cite
|
Sign up to set email alerts
|

High density of white‐faced capuchins (Cebus capucinus) and habitat quality in the Taboga Forest of Costa Rica

Abstract: Across the globe, primates are threatened by human activities. This is especially true for species found in tropical dry forests, which remain largely unprotected. Our ability to predict primate abundance in the face of human activity depends on different species' sensitivities as well as on the characteristics of the forest itself. We studied plant and primate distribution and abundance in the Taboga Forest, a 516‐ha tropical dry forest surrounded by agricultural fields in northwestern Costa Rica. We found th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 63 publications
(99 reference statements)
0
4
0
1
Order By: Relevance
“…The environmental variables driving differences in neopterin are probably not as simple as our captive vs. wild comparison implies. Notably, our wild population lives in an area of high anthropogenic disturbance ( 47 ) and animals in anthropogenic environments are often subject to increased risk of zoonotic disease and generally higher pathogen exposure ( 31 , 33 , 57 ). Difference in neopterin between wild and captive individuals may depend on degree of anthropogenic degradation in the wild environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The environmental variables driving differences in neopterin are probably not as simple as our captive vs. wild comparison implies. Notably, our wild population lives in an area of high anthropogenic disturbance ( 47 ) and animals in anthropogenic environments are often subject to increased risk of zoonotic disease and generally higher pathogen exposure ( 31 , 33 , 57 ). Difference in neopterin between wild and captive individuals may depend on degree of anthropogenic degradation in the wild environment.…”
Section: Discussionmentioning
confidence: 99%
“…The forest is surrounded by rice and sugarcane farmland that has been intensively cultivated for more than 30 years; approximately 40% of the forest is within 100 m of an anthropogenic edge. The Taboga Forest Reserve is an important piece of a fragmented biological corridor connecting the Tempisque River Basin to the Guanacaste Mountains ( 47 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, it was possible to estimate the individual and group density per transect and for the whole study area using the formulas established by the National Research Council (NRC, 1981; Table 1). This research had a total of nine focal encounters with Cebus imitator in the whole research area, which is a low number of encounters in comparison with some other studies of the species (Chapman et al,, 1988;Estrada and Coates-Estrada, 1996;Timock and Vaughan, 2002;Tinsley Johnson et al, 2020), but similar to the ones reported in the wildlife refugee centre "Rio Escalante-Chococente", in the south of Nicaragua (Williams- Guillén et al, 2013), although these authors mention their study was possibly an under-registration of encounters for the species in this area. Estimations obtained from a low number of encounters must be cautiously interpreted (Plumtre, 2000;Gonzales-Solis et al, 2001), but the data are especially relevant when there is no other information available for the species in the study area.…”
Section: Resultsmentioning
confidence: 99%
“…A. geofroyi adapt to fragmented landscape by increasing feeding time, eating less nutrient-rich food items (i.e., leaves) (Chaves et al, 2011), and reducing sub-group size (Rodriguez, 2017). S. imitator adapt to fragmented landscapes by socializing in larger groups in smaller home ranges (Tinsley Johnson et al, 2020).…”
Section: Study Areamentioning
confidence: 99%